Designing of Device for Endoscopic Surgery In Experimental Animals - Grebenyuk, A. I.; Chizh, N. A.; Byzov, D. V.; Rohoza, L. A.; Antonenko, E. A.; Lukyanenko, P. G.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):189.